Preoperative Cryotherapy Use in Anterior Cruciate Ligament Reconstruction - Koyonos, Loukas; Owsley, Kevin; Vollmer, Emily; Limpisvasti, Orr; Gambardella, Ralph (The Journal of Knee Surgery, 2014)
Unrelieved postoperative pain may impair rehabilitation, compromise functional outcomes, and lead to patient dissatisfaction. Preemptive multimodal analgesic techniques may improve outcomes after surgery. We hypothesized that patients using preoperative cryotherapy plus a standardized postoperative treatment plan will have lower pain scores and require less pain medication compared with patients receiving a standardized postoperative treatment plan alone after arthroscopically assisted anterior cruciate ligament reconstruction (ACLR). A total of 53 consecutive patients undergoing arthroscopically assisted ACLR performed by one of seven surgeons were randomly assigned to one of two groups. Group 1 received no preoperative cryotherapy and group 2 received 30 to 90 minutes of preoperative cryotherapy to the operative leg using a commercial noncompressive cryotherapy unit. Visual analog scale pain scores and narcotic use were recorded for the first 4 days postoperatively. Total hours of cold therapy and continuous passive motion (CPM) use and highest degree of flexion achieved were recorded as well. Group 1 consisted of 26 patients (15 allograft Achilles tendon and 11 autograft bone patellar tendon bone [BPTB]), and group 2 consisted of 27 patients (16 allograft Achilles tendon and 11 autograft BPTB). Group 2 patients reported less pain (average 1.3 units, p < 0.02) and used less narcotic use (average 1.7 tablets, p < 0.02) for the first 36 hours compared with group 1. No statistically significant differences were identified between the two groups with regard to demographics, hours of postoperative cryotherapy, hours of CPM use, or maximum knee flexion achieved. Complications did not occur in either group. This is the first report we are aware of showing the postoperative effects of preoperative cryotherapy. Our results support the safety and efficacy of preoperative cryotherapy in a multimodal pain regimen for patients undergoing ACL reconstruction.
Keywords: cryotherapy; multimodal pain management; ACLR; cold therapy